2001
DOI: 10.1097/00000658-200102000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Pulmonary ICAM-1 Expression Ameliorates Lung Injury in Established Diet-Induced Pancreatitis

Abstract: ObjectiveTo determine whether blocking the cell surface expression of intracellular adhesion molecules (ICAM-1) in established severe acute pancreatitis (AP) would ameliorate pulmonary injury. Summary Background DataLung injury in AP is in part mediated by infiltrating leukocytes, which are directed to lung tissue by ICAM-l. The authors' laboratory has previously demonstrated that AP results in overproduction of inflammatory cytokines, upregulation of pulmonary ICAM-1 expression, and a concomitant infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Depletion of circulating neutrophils with antineutrophil serum (9,22,23) or strategies that interfere with neutrophil migration, such as the use of a blocking antibody to ICAM-1 reduce neutrophil infiltration and pancreatic damage in acute pancreatitis (27,31).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of circulating neutrophils with antineutrophil serum (9,22,23) or strategies that interfere with neutrophil migration, such as the use of a blocking antibody to ICAM-1 reduce neutrophil infiltration and pancreatic damage in acute pancreatitis (27,31).…”
Section: Discussionmentioning
confidence: 99%
“…Although ICAM-1 is expressed constitutively at low levels on multiple cell types, its expression can be significantly increased in the presence of inflammatory cytokines such as interleukin (IL)-1, tumor necrosis factor-α, and shear stress [12,13,14,15,16]. In the lung, this expression has been illustrated in several animal models of acute lung injury, in which inhibition of ICAM-1 expression with blocking antibodies decreases leukocyte recruitment and parameters of lung injury [17,18,19,20]. Research groups have found that ICAM-1 also exists on alveolar epithelium [21].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the plasma levels of these soluble adhesion molecules reliably reflect the severity of disease, suggesting that they can serve as indicators. Anti-ICAM-1 antibody suppresses not only pancreatic damage, but also damage to the lungs which are located at a distance from the pancreas [13,14,21]. These results suggest that antibodies against adhesion molecules may be potentially useful in the treatment of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 83%